2015
DOI: 10.12659/ajcr.893849
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Tumor of the Patella Tendon Sheath Presenting as a Painful Locked Knee

Abstract: Patient: Male, 26Final Diagnosis: Giant cell tumor of the patella tendon seathSymptoms: Efusion • locking knee • painMedication: NoneClinical Procedure: Arthroscopy and open resection of the tumorSpecialty: Orthopedics and TraumatologyObjective:Rare diseaseBackground:The giant cell tumor of the tendon sheath (GCT-TS) is a benign proliferative synovial tumor manifesting as an intra-articular solitary nodule. When it involves the infrapatellar fat pad it can present acutely as a painful locked knee.Case Report:A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Due to nonspecific signs and symptoms, diagnosis of a giant cell tumor can be delayed for weeks or months. The common concerns may include painless or painful palpable swelling, joint effusion, locking of the knee joint, and restriction of movement [1,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to nonspecific signs and symptoms, diagnosis of a giant cell tumor can be delayed for weeks or months. The common concerns may include painless or painful palpable swelling, joint effusion, locking of the knee joint, and restriction of movement [1,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of a large tumor of this size (in the infrapatellar region) have been reported in the literature [1,3,7,9]. Panagopoulos et al reported a case of a giant cell tumor measuring 5 cm [8]. Radiographs are of little help in diagnosing giant cell tumors because they are normal for a majority of the time, but sometimes an opacity may be observed in the infrapatellar region [1,2,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most cases of locked knee are due to intra-articular blockade caused by an unstable meniscal tear, anterior cruciate ligament (ACL) tear, or chondral lesion resulting in a loose bodies. Although they are very rare, benign intra-articular tumors or tumor-like lesions can also cause the knee to lock [ 1 , 2 ]. In this case, we present a rare case of a locked knee that was caused by fat pad adhesion after injury.…”
Section: Introductionmentioning
confidence: 99%